Unregistered Traditional Bone Setting Practice in Aceh, Indonesia: A Problem that Need to be Solved? - Safrizal Rahman; Azharuddin Azharuddin; Amanda Yufika; Rovy Pratama (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
Little is known about traditional bone setting (TBS) practise in Aceh, Indonesia despite of its common utilisation. The aim of this study was to explore the characteristics of TBS practise in Aceh, Indonesia. Thirty-nine participants from ten regencies in Aceh were interviewed from January to December 2019. Most of the participants were male (82.1%), and aged between 31-50 years old (79,5%). Half of the participants were elementary school graduates (51,3%). More than half (59%) of participants had been practicing bone setting for 5-10 years, and many of them (48.7%) used traditional massages combined with splints and herbal mixtures. None (0%) of the participant obtained legal permission to practice bone setting. More than half (71.8%) obtained the knowledge of TBS from their ancestral heritage, only one participant obtained it through apprenticeships. We concluded that TBS practices in Aceh were unregistered, and the practitioners were mostly untrained. There is a need to provide training and permits for TBS practise to ensure patients’ safety.